Crocin as a novel therapeutic agent against colitis. (2nd September 2020) - Rezaei, Nastaran; Avan, Amir; Pashirzad, Mehran; Rahmani, Farzad; Moradi Marjaneh, Reyhaneh; Behnam-Rassouli, Reihane; Shafiee, Mojtaba; Ryzhikov, Mikhail; Hashemzehi, Milad; Ariakia, Fatemeh; Bahreyni, Amirhossein; Hassanian, Seyed Mahdi; et al.
Abstract: Ulcerative colitis is a chronic inflammatory bowel disease with high incidence and prevalence worldwide. To investigate the therapeutic potency of crocin, as a pharmacologically active component of saffron, in dextran sodium sulfate (DSS)-induced colitis mice model. Experimental colitis was induced by 7-day administration of DSS dissolved in water at a concentration of 1.5% (w/v). The animals were randomly divided into four groups (n¼6 for each group). (1) Control group received regular drinking water for four weeks, (2) the second group of mice received regular drinking water for three weeks and then received DSS for one week, (3) and (4) the other two groups received 50-ppm or 200-ppm crocin for three weeks, respectively, and then treated with DSS for one week. Our results showed that Crocin attenuates colitis disease activity index including body weight loss, diarrhea, rectal bleeding, and colon shortening in crocin pre-tread mice. Comparison of histology of colon tissues between groups showed that crocin significantly decreases colon histopathological score, at least partially, by eliciting anti-inflammatory responses in DSS-induced colitis mice. These results clearly showed that crocin is a novel therapeutic agent with low toxicity as well as great clinical significance in treatment of colitis.